PENERAPAN BALANCED SCORECARD SEBAGAI PENGUKUR KINERJA MANAJEMEN PADA PT MATAHARI DEPARTMENT STORE TBK - Nindy Livia Luciawanty; Ari Christanti (Fakultas Bisnis UKDW, 2011)
This study aims to determine the performance of PT. Matahari Department Store using the Balanced Scorecard. This measurement is looking at the business unit from four perspectives: financial, customer, internal business processes, and learning- growth. The analysis showed that: 1) In Financial perspective, which seen from the growth of revenue, ROI (Return onInvestments), and profit margin shows the performance of PT. Matahari Department Store is good; 2) In The customer perspective reflects a good employee performance against customer service with the MCC (Matahari Club Card) card services and VOC (Voice Of Customer) 3) In Internal business perspective from the company's innovation and after sales service, the overall performance of the company's management has shown good results; 4) In Learning and growth perspective about the level of employee satisfaction showed good results by the awards given by companies to employees’s performance through Customer Service All-Star and training to employeesKeywords: balanced scorecard, performance